ANALISIS KONTRASTIF KATA KERJA BERDASARKAN WAKTU DALAM BAHASA ARAB DENGAN BAHASA PALEMBANG - Suharsono Suharsono; Ami Rahmat Ami Rahmat (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
This article is aim to describe the difference between Arabic fi'il and Palembang language verbs from the aspect of adverbs of time. The method of this research is qualitative in the form of contrastive analisis. the collecting data, this research used a contrastive synchronic research method. The stages in this research are the stages of providing data, then the data obtained is analyzed, then after being analyzed the data will be presented. The data used are several vocabularies that contain information about time in both the Palembang language and Arabic. The result of this research is the difference in the adverbs of time used in the two languages, both past, present and future.